Innovative business plan: dez melhores opiniões online review platform - Jerez, Joaquin Texeira (2021)
The objective of this master thesis - "Dez melhores opiniões" - is to develop an innovative business plan to study the viability and development of an online comparison platform in Portugal to enable consumers to inform themselves before buying a product. We want to establish a loyal community of participative users in order to create accurate, reliable and objective information, in an era where Internet is the main transmitter of fake and biased information. The idea of this project comes from Joaquin Texeira and Arturo Carpio, colleagues from University Francisco de Vitoria in Madrid, where they studied the degree in Business Management together. Both aware of the digital environment, the motivation of the project arose from the concern of the ethical lack existent in the online surroundings and the mass media. For this purpose, the project reviews, through the literature review, the academic concept deriving from online reviews and their influence: Electronic Word of Mouth - eWOM. Afterwards, the project focus on the study of the environment where the activity would be developed, with the evaluation of competitors, consumers, marketing mix strategies and different determinant factors of its viability. Once developed and presented the competitive advantage of the project, the conclusion is that the project is viable with a forecast of 4 years, where the investment of resources and capabilities in the company will allow it to define the second phase of the project. The Technological, Human Resources, Fiscal and Juridical plans have been carried out to enable the company to compete and survive in the market. Finally, the Financial-Economical plan reflects the monetary flux and viability of the project in its first phase.